Catheter to vein ratio and risk of peripherally inserted central catheter (PICC)-associated thrombosis according to diagnostic group: a retrospective cohort study. Issue 7 (5th July 2021) - Sharp, Rebecca; Carr, Peter; Childs, Jessie; Scullion, Andrew; Young, Mark; Flynn, Tanya; Kirker, Carolyn; Jackson, Gavin; Esterman, Adrian
Abstract : Objectives: Determine the effect of the catheter to vein ratio (CVR) on rates of symptomatic thrombosis in individuals with a peripherally inserted central catheter (PICC) and identify the optimal CVR cut-off point according to diagnostic group. Design: Retrospective cohort study. Setting: 4 tertiary hospitals in Australia and New Zealand. Participants: Adults who had undergone PICC insertion. Primary outcome measure: Symptomatic thrombus of the limb in which the PICC was inserted. Results: 2438 PICC insertions were included with 39 cases of thrombosis (1.6%; 95% CI 1.14% to 2.19%). Receiver operator characteristic analysis was unable to be performed to determine the optimal CVR overall or according to diagnosis. The association between risk of thrombosis and CVR cut-offs commonly used in clinical practice were analysed. A 45% cut-off (≤45% versus ≥46%) was predictive of thrombosis, with those with a higher ratio having more than twice the risk (relative risk 2.30; 95% CI 1.202 to 4.383; p=0.01). This pattern continued when only those with malignancy were included in the analysis, those with cancer had twice the risk of thrombosis with a CVR greater than 45%. Whereas the 33% CVR cut-off was not associated with statistically significant results overall or in those with malignancy. Neither the 33% or 45% CVR cut-off produced statistically significant results in those with infection or other non-malignant conditions. Conclusions: Adherence to CVR cut-offs are an important component of PICC insertion clinical decision making to reduce the risk of thrombosis. These results suggest that in individuals with cancer, the use of a CVR ≤45% should be considered to minimise risk of thrombosis. Further research is needed to determine the risk of thrombosis according to malignancy type and the optimal CVR for those with a non-malignant diagnosis.